PENGARUH LINGKUNGAN KERJA, MOTIVASI, DAN KEMAMPUAN TERHADAP KINERJA PEGAWAI (Study Kasus Pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Malang) - Ridho Hananta Ramadhan; Rois Arifin (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThis study aims to determine and analyze the influence between work environment, motivation and ability to the performance of employees partially and simultaneously. This type of research is a quantitative research. Respondents in this study are employees in the Regional Financial and Asset Management Agency of Malang Regency. The sample used in this study amounted to 53 employees. Data collection method used is to spread the questionnaire and interview. The results showed that the work environment variables and the ability to affect the performance of employees partially. While the variable of motivation does not affect the variable performance of employees partially. Simultaneously work environment variables, motivation and ability affect the performance of employees.Key words: performance, work environment, motivation, ability